Video-supported collaborative learning: A literature review towards the identification of sound pedagogical models for conceptual thinking and professional development - Ramos, José (2020)
Although for many people video is proven to be central both in private and professional life as a means to communicate, to entertain, and to learn, when it comes to this last function the available and established pedagogical models refer more easily to individual than to collaborative instructional strategies. In order to fill this gap, we conducted a structured literature review to scan how video technologies have been used to support collaborative learning in order to facilitate professional development, as well as which models of collaboration have been successfully established. 474 contributions have been screened, 100 of which were finally included in a detailed review. Results highlight 5 different ways of using video for supporting collaborative learning, as well as 13 underlying pedagogical approaches, the combination of which will give directions for building practice-oriented design principle on the effective implementation of video-supported collaborative learning.